Imaging Characteristics and Surgical Outcomes in Patients With Intraspinal Solitary Fibrous Tumor/Hemangiopericytoma: A Retrospective Cohort Study. Issue 2 (March 2023) - Okubo, Toshiki; Nagoshi, Narihito; Tsuji, Osahiko; Tachibana, Atsuko; Kono, Hitoshi; Suzuki, Satoshi; Okada, Eijiro; Fujita, Nobuyuki; Yagi, Mitsuru; Matsumoto, Morio; Nakamura, Masaya; Watanabe, Kota
Study Design: Retrospective cohort study. Objectives: Intraspinal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) is often misdiagnosed preoperatively as schwannoma or meningioma because its imaging characteristics are not well understood. As postoperative prognosis differs among the 3 lesions, predicting the probability of SFT/HPC preoperatively is essential. Thus, this study investigates the imaging characteristics of SFT/HPC compared with those of schwannoma or meningioma and evaluates surgical outcomes. Methods: The preoperative imaging findings, tumor resection extent, recurrence and regrowth rates, and neurological improvement were compared between 10 patients with SFT/HPC and 42 patients with schwannoma or 40 patients with meningioma. Results: Most patients with SFT/HPC showed isointensity on both T1- and T2-weighted images compared with patients with schwannoma ( P = 0.011 and 0.029, respectively) and no significant difference compared with patients with meningioma ( P = 0.575 and 0.845, respectively). Almost all patients with SFT/HPC showed highly uniformizing enhancement patterns, similar to those with meningioma ( P = 0.496). Compared with meningioma, SFT/HPC lacked the dural tail sign and intratumoral calcification and exhibited irregular shape. Of the 5 patients who underwent partial resection, 60% exhibited tumor recurrence and regrowth following surgery. Conclusions: Complete en bloc surgical resection should be attempted in patients with intraspinal SFT/HPC to prevent postoperative recurrence or regrowth. As this tumor is often preoperatively misdiagnosed, we recommend that the imaging findings exhibited in this study should be used to positively suspect SFT/HPC. This will enhance patient outcomes by enabling more appropriate preoperative surgical planning.